STUDY OF ON THE ELECTROCHEMICAL BEHAVIOR OF TITANIUM IN ACIDIC BROMIDE SOLUTION BY RECORDING THE POTENTIODYNAMIC POLARIZATION CURVES - R.N. Nurdillayeva; A.B. Bayeshov; Sh.H. Khabibullayeva (Academic Scientific Journal of Chemistry, 2019)
The electrochemical dissolution of titanium in a potassium bromide solution acidified with a sulfuric acid solution by recording cyclic and anodic potentiodynamic polarization curves was studied for the first time. The influence of the sulfuric acid and potassium bromide solutions concentration on the titanium electrode oxidation was considered. A polarization curve was performed in 1.0 M potassium bromide solution in the presence of 0.5 M sulfuric acid and the titanium oxidation anodic maximum was recorded. To explain the titanium dissolution characteristics during the polarization by industrial alternating current, cyclic anodic-cathodic (CAC) and cyclic cathode-anodic (CCA) polarization curves of the titanium electrode in potassium bromide sulfate solution were recorded. At the CAC voltammogram, when the titanium potential is shifted to the anode direction, titanium oxidation current is recorded at potentials from “plus” 1.3 V to “plus” 2.3 V. In the cathode direction of the CCP voltammogram curve between potentials “minus” 0.7–1.0 V, a hydrogen evolution current is observed. The dependence of anodic potentiodynamic polarization curves on the concentration of sulfuric acid and potassium bromide solutions was studied, in both cases an increase in the titanium oxidation maximum current was observed, a mechanism was also established and the reactions sequence proceeding on the electrode was calculated. Studies have shown that electrode reactions occur by a complex mechanism